2019
DOI: 10.1111/dar.12987
|View full text |Cite
|
Sign up to set email alerts
|

Availability of licensed cannabis businesses in relation to area deprivation in Washington state: A spatiotemporal analysis of cannabis business presence between 2014 and 2017

Abstract: Introduction and Aims In states where recreational use of cannabis has been legalised, increasing numbers of cannabis licensed cannabis businesses resulted in concerns about their potential social and health impacts. This study examined spatiotemporal variations in availability of cannabis licensed cannabis businesses (i.e. producers, processors and retailers) in relation to area deprivation in Washington state from 2014 to 2017. Design and Methods Data on licensed cannabis businesses were obtained from the Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Other studies have focused on geospatial locations of medical or recreational cannabis dispensaries, not certifying providers. While most of these studies report that dispensaries were more commonly located in neighborhoods with high levels of poverty or deprivation, or high percentages of Black or Hispanic residents [ 33 37 ], one study reported no relationship between locations of dispensaries and these neighborhood characteristics [ 38 ]. There are several potential reasons for the differences in findings between these studies and ours.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on geospatial locations of medical or recreational cannabis dispensaries, not certifying providers. While most of these studies report that dispensaries were more commonly located in neighborhoods with high levels of poverty or deprivation, or high percentages of Black or Hispanic residents [ 33 37 ], one study reported no relationship between locations of dispensaries and these neighborhood characteristics [ 38 ]. There are several potential reasons for the differences in findings between these studies and ours.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational cannabis outlets are disproportionately located in neighborhoods with high proportions of low-income and racial-ethnic minority residents. [15][16][17][18][19] Policies that encourage greater reductions in outlets in vulnerable neighborhoods therefore have the potential to promote health equity.…”
mentioning
confidence: 99%
“…That is, the differences in the density of stores and their proximity to schools, and potentially other places where youth and other vulnerable groups are likely the main populations, are likely following the same differential patterns. Moreover, research in Canadian jurisdictions and in some US states (e.g., Colorado, California, Washington, and Oregon), also found higher stores per capita in neighborhoods with a larger proportion of racial or ethnic minorities, lower household income, and medium to high crime index (Amiri et al., 2019; Firth et al., 2019; Myran et al., 2021; Shi et al., 2016; Unger et al., 2020).…”
Section: Discussionmentioning
confidence: 99%